Active vitamin D increases myogenic differentiation in C2C12 cells via a vitamin D response element on the myogenin promoter - Alliband, Kathryn H.; Parr, Tim; Jethwa, Preeti H.; Brameld, John M. (Frontiers in Physiology, 2024)
Background Skeletal muscle development during embryogenesis depends on proliferation of myoblasts followed by differentiation into myotubes/multinucleated myofibers. Vitamin D (VD) has been shown to affect these processes, but there is conflicting evidence within the current literature on the exact nature of these effects due to a lack of time course data. With 20-40% of pregnant women worldwide being VD deficient, it is crucial that a clearer understanding of the impact of VD on myogenesis is gained. Methods A detailed 8-day differentiation time course was used where C2C12 cells were differentiated in control media (2% horse serum) or with different concentrations of active VD, 1,25(OH)2D3 (10 -13 M, 10 -11 M, 10 -9 M or 10 -7 M), and measurements were taken at 6 time points. DNA, creatine kinase and protein assays were carried out as well as quantitative PCR to determine expression of Myf5, MyoD, myogenin, MHC I, MHC neonatal, MHC embryonic, MHC IIa, MHC IIx and MHC IIb mRNAs. Transfections were carried out using one vector containing the myogenin promoter and another containing the same promoter with a 3 base mutation within a putative vitamin D response element (VDRE) to determine effects of 1,25(OH)2D3 on myogenin transcription. Finally, a ChIP assay was performed to determine whether the VD receptor (VDR) binds to the putative VDRE. Results 1,25(OH)2D3 caused an inhibition of proliferation and an increase in differentiation in C2C12 cells. Myf5, myogenin, MHC I, MHC neonatal, MHC embryonic, MHC IIa, MHC IIx and MHC IIb expression were all increased by 1,25(OH)2D3. Myotube size was also increased by VD. When the putative VDRE on the myogenin promoter was mutated, the increase in expression by VD was lost. ChIP analysis revealed that the VDR does bind to the putative VDRE on the myogenin promoter. Conclusions Active VD directly increases myogenin transcription via a functional VDRE on the myogenin promoter, resulting in increased myogenic differentiation, increased expression of both the early and late MHC isoforms, and also increased myotube size. These results highlight the importance of VD status during pregnancy for normal myogenesis to occur, but further in vivo work is needed.